Einheitliche Produktnamen für den gesamten SPNV in Deutschland. Eindeutige Kennzeichnung statt Begriffssalat. - Grunberg, Bastian; Schaffer, Thomas (Alba, 2010)
S-Bahn, RE und RB sind Marken der Deutschen Bahn AG, werden jedoch ab sofort auch allen anderen Unternehmen zur Verfügung stehen. Möglich wird dies durch eine Lizenzierung der Markenrechte. Dies haben DB AG und BAG SPNV in den vergangenen Monaten verhandelt.

S-Bahn, RE and RB are registered trademarks owned by Deutsche Bahn AG (DB). The trademarks are now going to be applied to every passenger railway transportation company in Germany. The DB AG gives a trademark licence by a licence agreement which is result of negotiations between DB AG and BAG SPNV during the last months.
Unified trademarks for the complete short distance railway sector in Germany.
Keywords: Verkehr; Stadtverkehr; Regionalverkehr; Schienenverkehr; Verkehrsunternehmen; Marketing; Kennzeichnung; Markenzeichen; Vereinheitlichung; Lizenz; Corporate Design